Discovery of sapphirine-bearing Mg-Al granulites in the North China Craton: Implications for paleoproterozoic ultrahigh temperature metamorphism - Santosh, M.; Tsunogae, T.; Li, J. H.; Liu, S. J. (Gondwana Research, 2007)
We report here for the first time the occurrence of Mg-Al granulites within the khondalite belt of the North China Craton and provide robust evidence for extreme crustal metamorphism at ultrahigh-ternperature (UHT) conditions in this region. The UHT indicator assemblages in these rocks include equilibrium sapphirine +quartz, high alumina orthopyroxene +sillimanite +quartz and high temperature perthites. The surrounding khondalites also carry spinel+ quartz equilibrium assemblage. The sapphirines occurring in various micro structural associations are markedly magnesian (X(Mg)-0.69-0.77) with a cornposition varying from 7:9:3 to 2:2:1 end members. Spinel is a solid solution of Mg-spinel and hercynite (X(Mg)-0.41-0.54) with ZnO content varying from 0.48 to 1.79 wt.%. Garnet shows a compositional range between pyrope and almandine (X(Mg)-0.39-0.48) with minor grossular (2.6-3.8 mol%) and spessartine (0.5-1.8 mol%). The orthopyroxenes display marked compositional variations in terms of Al(2)O(3) content, with the core of the medium-grained orthopyroxene adjacent to sillimanite in the matrix showing the highest Al(2)O(3) content (8.4 wt.%). The history of prograde to peak metamorphism of these rocks is indicated by inclusions of sapphirine, spinel, quartz and sillimanite within garnet. Sapphirine formed during the peak stage through the reaction: Spl +Qtz+ Sil -> Spr. Occurrence of sapphirine and quartz inclusions trapped in sillimanite suggests the reaction: Spr+Qtz+Grt -> Opx+Sil. A series of retrograde reactions are observed in these rocks as corona and symplectite textures around early coarse-grained minerals such as: Opx + Sil + Qtz -> Crd, Grt + Sil + Qtz -> Crd, Grt + Qtz -> Crd + Opx, Grt+O(2)-> Crd+Qtz+Fe(2)O(3) in Mag or Ilm, and finally Opx+Kfs+H(2)O -> Bt+Qtz. Whereas the stability of sapphirine +quartz and orthopyroxene + sillimanite+ quartz in the matrix assemblage suggests T > 1000 degrees C and P > 10 kbar peak metamorphism, conventional geothermobarometric estimates confirm the ultrahigh-temperature nature and also trace the retrograde conditions (930-970 degrees C at P > 10 kbar Al in Opx; 900-1000 degrees C - perthite; 930-990 degrees C - Grt-Opx; and 910-940 degrees C - sapphirine-spinel). Electron microprobe dating of monazites in textural association with the UHT assemblages yield a sharply defined isochron age of 1917 +/- 48 Ma, which correlates with the 1927 +/- 11 Ma obtained in a previous study from monazites in the surrounding khondalites carrying spinel+quartz assemblage. An evaluation of the assemblages and textures using appropriate petrogenetic grids indicate that following peak ultrahigh temperature conditions, the rocks underwent initial isobaric cooling and subsequent isothermal decompression, and we interpret these trajectories to be part of an overall anti-clockwise P-T evolution. The study area, located within the northern margin of the North China Craton, defines a collisional orogenic belt where continental collision and deep subduction was possibly followed by extensional collapse of the orogen. Evidence for the extensional phase is provided by the several mafic magmatic intrusives of Paleoproterozoic age occurring in the region which suggest a possible link between the thermal anomaly associated with extreme crustal metamorphism in this region with mantle-derived magmas. The UHT metamorphism in North China Craton coincided with the assembly of the Paleoproterozoic supercontinent Columbia. (c) 2006 International Association for Gondwana Research. Published by Elsevier B.V All rights reserved. Geosciences, Multidisciplinary SCI(E) 0 ARTICLE 3 263-285 11